UPAYA MENINGKATKAN KETERAMPILAN SISWA TENTANG MENYUSUN LAPORAN KEUANGAN PADA SISWA KELAS XI IPS 5 SMAN 3 KETAPANG MELALUI METODE SIMULASI - Yustandar, Agus (Jurnal Visi Ilmu Pendidikan, 2020)
Classroom Action Research is based on the fact that students' ability to understand financial statements is still low. Whereas with the mastery of Economics in general students do not have difficulty learning other subjects. This observation took place in January to May 2017, because in those months students have completed general semester examinations and are still at the beginning of the semester so that student conditions can be observed from the beginning. Simulation method is a learning method wherein the teaching and learning process the teacher invites students to group together in completing assignments in class and allows students to find information that is traditionally informed or disguised. From this study it can be concluded that with the motivation in learning simulation learning methods the ability of students to compile financial statements and learning outcomes will be optimal. The more precise the motivation given, the more successful the lesson will be. With high motivation, the intensity of student learning efforts will also be high. So motivation will always determine the intensity of student learning. This will improve student learning achievement.Keywords: Compiling Financial Statements, Simulation Methods